Nilai-Nilai Simbolik dalam Kesenian Tradisional Betingkah Alu Selesung di Desa Ceruk Bunguran Timur Laut Kabupaten Natuna, Provinsi Kepulauan Riau - saputra, al.iklas febriyan (Estoria: Journal of Social Science and Humanities, 2025)
Traditional arts are a cultural system that lives and develops in society as a form of expression that emerges from within the community. The development of the times has caused changes in all fields, including art. Traditional arts began to be neglected and finally destroyed and replaced by modern art. This research aims to find out: the history of the art of Betingkah Alu Selesung and its symbolic meaning in the traditional art of Betingkah Alu Selesung on Bunguran Island in general and Ceruk Village, Northeast Bunguran, Natuna Regency in particular. This research uses a qualitative descriptive method of analysis, qualitative research has two main things, namely: describe-reveal and describe-explain. Data collection by means of observation, interviews, documentation, and literature studies. Data analysis includes: data reduction, data presentation, and verification. The results of the study concluded that the art of Betingkah Alu Selesung has existed since ancient times every harvest season. According to   oral history, this art was created from the king's competition so that there was an art that could entertain the community. The symbolic meanings contained in this art include: Betingkah Alu Selesung means hitting a mortar; alu-mortar is a symbol of gender, a symbol of fertility; togetherness, Betingkah Alu Selesung cannot be done alone, must be done in groups; the shape of the pestle symbolizes the cardinal direction; and religiously, this art is an expression of gratitude for the harvest to God Almighty.Keywords: Symbolic, Artistic, and Traditional